Using ChatGPT in the French Language Course for Veterinary Students - Elena Velescu (Linguaculture)
The emergence of many forms of free tools and applications, easy to use thanks to the «chatbot» format, based on Generative Artificial Intelligence, such as ChatGPT, has forced the reflection on their use in education and training. Such a tool, capable of expressing itself in a coherent language and with a large amount of information at its disposal, is a non-negligible asset for a language teacher. In addition, in a foreign language course (French) adapted to a professional audience with specific needs, the help obtained by using such tools can be extremely valuable in saving time and resources. In this article, I will show some practical possibilities of using ChatGPT for the French language course adapted to students of Veterinary Medicine at the University of Life Sciences «Ion Ionescu de la Brad» in Iasi.